Preoperative Concerns in Patients Undergoing Endoscopic Sinus Surgery: A Multi‐institutional, Prospective Study. (23rd August 2013) - Yeung, Jeff; Brandt, Michael G.; Rotenberg, Brian; Franklin, Jason H.; Kilty, Shaun; Doyle, Philip
Abstract : Objectives: Patient‐centered care is recognized as being fundamental to successful medical practice. The effectiveness of patient‐centered care has classically been measured by post‐treatment outcomes, such as patient compliance and psychosocial responses. To date, systematic assessment of patient concerns prior to treatment has been limited. Functional endoscopic sinus surgery (FESS) is an elective surgery for chronic sinusitis that carries a clear, defined set of risks. This study aimed to determine the concerns of patients undergoing FESS for chronic sinusitis. Methods: Study Design: Multi‐institutional, prospective survey of patient concerns. Methods: Two hundred patients undergoing endoscopic sinus surgery for chronic rhinosinusitis with or without polyposis were recruited. They completed a validated survey assessing their concerns regarding the risks and outcomes of surgery. Data were analyzed using descriptive statistics. Results: Generally, patients had a low degree of concern prior to undergoing surgery, though significant individual variability existed. Subjects felt the greatest level of concern regarding potential need for revision surgery and wait time for surgery. Additionally, rare post‐operative complications, such as orbital injury and cerebrospinal fluid leak, generated higher levels of concern. Conclusions: Patient concern prior to undergoing elective surgery is generally low. However, patients' areas of greatest concern may not align with those perceived by the physician. Our findings highlight topics that require careful discussion during the informed consent process for patients undergoing FESS.